THE CORRELATION OF THE FAME OF WINE REGIONS AND WINE GASTRONOMY FESTIVALS IN THE PANNON WINE REGION - Závodi, Bence; Szabó, Géza (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Due to the change in consumption trends, the interest in wine gastronomy festivals has continuously increased in the recent years. The basis of the increased demand was the expanding supply of festivals. In our opinion the wine gastronomy festivals may play a significant role in the improvement of the reputation of wine producing areas, but this potential in not used to the same extent in the various wine regions of Hungary. During our research we collected and analysed the findings of surveys conducted in recent years on the reputation of the Hungarian wine producing areas. From different sources we collected the wine gastronomy festivals of Hungary, and then we used the database compiled for the definition of the major, especially geographical and thematic features of the supply. We found several exemplas that well demonstrate the correlation between the fame coming from the reputation of the wine producing areas and the number of the wine gastronomy festivals. The Pannon Wine Region is one of the enological tourism centres of Hungary from both (wine) professional and tourism aspects, but we have to emphasise that the wine producing areas within the wine region have different levels of involvement in enological tourism